Hubungan Lama Pemakaian Soft Contact Lens dengan Keluhan Sindrom Mata Kering - Putu Febi Apriliona; Nyoman Sunariasih; Rima Kusuma Ningrum (Aesculapius Medical Journal, 2022)
Contact Lenses are one of the popular specialized innovations in the field of ophthalmology which very common in society. This is supported by the large number of contact lens wearers worldwide, which has reached 125 million people, while the prevalence of eyeglass/contact lens wearers in Indonesia reaches 2.9% between the 15â€“24-year age group. Now contact lenses are not only seen as health aids but also as products that can support the lifestyle and the cosmetic field. The type of contact lens that is widely used is Soft Contact Lens (SCL) with various lengths of use ranging from daily to yearly. The purpose of this study was to determine the relationship between the duration of wearing soft contact lenses with complaints of dry eye syndrome. This study was a quantitative analytic study with a cross-sectional approach using purposive sampling. The research was conducted on 2017-2020 students at the Faculty of Medicine and Health Sciences, Warmadewa University with a total of 68 respondents. The data collection method used the Contact Lens Dry Eye Questionnaire-8 (CLDEQ-8) questionnaire. Data were analyzed univariate and bivariate using chi-square statistical test and then followed by Spearman's rank correlation test to determine the degree of relationship. The average duration of daily use of soft contact lenses is 7.58Â±2.711 hours. The study found that the P-value exceeded the significance level of 0.05 (P = 0.965) and the r-value was 0.005. The conclusion is there is no relationship and very weak correlation between the length of using soft contact lenses and complaints of dry eye syndrome.